Cardiopulmonary exercise testing in pulmonary arterial hypertension and chronic thromboembolic pulmonary hypertension - Alexis Coulis; Shir Levanon; Gurshaun Randhawa; Yevgeniy Brailovsky; Farhan Raza; Estefania Oliveros (Frontiers Media S.A., 2024)
Cardiopulmonary exercise testing allows for a comprehensive assessment of the mechanism of exercise limitation in pulmonary arterial hypertension and chronic thromboembolic pulmonary hypertension. Competitive pathophysiologic mechanisms may affect the clinical interpretation of cardiopulmonary disease as they relate to dyspnea, leg fatigue, and exercise intolerance.